877. ANDIRA ANTHELMIA: Leguminosae–Papilionoideae. (12th September 2018) - Pennington, R. Toby; de Lima, Haroldo C.; Watherston, Neil; Inches, Fiona
Summary: The history, taxonomy, distribution, habitat and cultivation requirements of the unusual legume tree Andira anthelmia (Vellozo) J.F. MacBride, are discussed; a full botanical description, pollination, colour illustration and dissection drawings are also provided.